The supplier management handbook - Bossert, James L., 1951- (ASQ Quality Press, 2004)
This new edition of the Supplier Management Handbook addresses the evolving role of the purchasing agent and discusses the future of customer-supplier relationships. Specifically, the book provides an overview of several basic supplier management issues including: specifications, record keeping, site inspection, measurement assurance, supplier rating, communications, ship-to-stock versus just-in-time, and data evaluation. This handbook serves as a comprehensive resource for any quality professional needing to identify a step-by-step process for supplier certification, including how to do a service certification. Two certification approaches are described as well as how to conduct a supplier survey and evaluate a supplieres product. Several chapters focus on specific supplier management applications including establishing effective quality control for the small supplier, procurement quality in the food industry, management of service suppliers, and software supplier management. Appendices include procurement quality definitions, audit guidelines, food industry associations, and federal government agencies involved with food safety. Preview a sample chapter from this book along with the full table of contents by clicking here. You will need Adobe Acrobat to view this pdf file.